Personal Relationships and Intimacy in the Age of Social Media - Miguel, Cristina (Springer International Publishing, 2018)
This book examines how intimate relationships are built, negotiated and maintained through social media. The study takes a cross-platform approach, analysing three social media platforms of different genres - Badoo, Couchsurfing and Facebook - and exploring two interactive forces that shape the way people communicate through social media: the platforms' architecture and policies, and actual practises of use. Combining analysis of the political economy of social media with users' perspectives of their own practises - as well as exploring the tensions between the two - the book provides a detailed picture of intimacy as a complex structure of continuity and change.